Investigation on an Innovative Internally Cooled Smart Cutting Tool With the Built-In Cooling-Control System - Ozturk, Erkan; Yildizli, Kemal; Saglam, Fatih (Springer Heidelberg, 2021)
There is a growing demand for sustainable and health-friendly chip removal applications in manufacturing industries. Internally cooled cutting tool (ICCT) designs promise low cost, eco-friendly cooling and no hazardous health effects. However, the ICCTs neither can estimate insert tip temperature (T-tip) precisely nor fix T-tip in determined temperature range by operator with controlling cooling of the insert. Within this, the machining quality of metallic materials can improve. For this reason, a new internally cooled smart cutting tool built-in cooling-control system (ICSCT) has been designed and manufactured for the turning operations. In this framework, a cutting tool has been modified with a new self-designed seat which has an inclined gap to spray the cutting fluid below the insert tip. Then, an innovative cooling-control system has been integrated to the cutting tool. An original and developable computational fluid dynamics (CFD)-statistic calibration method has been revealed to estimate T-tip. According to the calibration method enhanced with coding self-working strategy, the ICSCT can calculate T-tip by measuring the flank surface temperature (T-f), inlet temperature (T-inlet) and inlet velocity (v(f)). In conclusion, the ICSCT could decrease T-tip by up to 107 degrees C compared to no cooling in experiments. Whilst v(f) went up, T-f showed a decreasing trend. Whilst T-inlet went up, T-f values increased. Moreover, 1040 steel workpieces were machined and the average surface roughness from turning with the ICSCT was measured significantly less than dry turning under the same cutting parameters.
Sağlam, Fatih/0000-0002-2084-2008;
Keywords: Internal Cooling; Smart Tool; Cutting Tool; Sustainable Machining; Smart Machining